2014
DOI: 10.3928/01484834-20140805-02
|View full text |Cite
|
Sign up to set email alerts
|

Use of Photovoice to Integrate a Community-Engaged Scholarship Model of Research Into an Undergraduate Clinical Nursing Course

Abstract: For undergraduate nursing students to appreciate the underpinnings of research, it is essential to bring research to real-life clinical practice. This article reports on an innovative educational experience integrating qualitative research into the sophomore-level clinical setting. The elements of this pedagogical approach within the context of faculty-mentored and student-led community-based participatory research are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…For example, Gallagher and Stevens (2015) taught nursing students about social justice in the classroom, then connected the theory to their clinical experiences by instructing students to take photographs of their community during a windshield survey. Similar to the findings of a study with social work students by Monteblanco and Moya (2021), we found that photovoice can serve as an introduction to the topic of nursing research, especially qualitative methodologies (Braband & Warren‐Mears, 2017; Kronk & Weideman, 2014). Despite being undervalued in the curricular development of “hard sciences,” learning in the affective domain has the potential to promote emotional intelligence, stress management, and clinical decision‐making, potentially facilitating nursing students' transition to practice as well as improving retention and supporting positive patient outcomes (Bulmer Smith et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…For example, Gallagher and Stevens (2015) taught nursing students about social justice in the classroom, then connected the theory to their clinical experiences by instructing students to take photographs of their community during a windshield survey. Similar to the findings of a study with social work students by Monteblanco and Moya (2021), we found that photovoice can serve as an introduction to the topic of nursing research, especially qualitative methodologies (Braband & Warren‐Mears, 2017; Kronk & Weideman, 2014). Despite being undervalued in the curricular development of “hard sciences,” learning in the affective domain has the potential to promote emotional intelligence, stress management, and clinical decision‐making, potentially facilitating nursing students' transition to practice as well as improving retention and supporting positive patient outcomes (Bulmer Smith et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…According to Wang and Burris (1997), an important objective of photovoice research is to share pertinent health and community issues with policymakers; however, few articles incorporated this aspect. Of the 22 included studies, five (Andina‐Díaz, 2020; Gallagher & Stevens, 2015; Kronk & Weideman, 2014; Solano‐Ruiz et al, 2021; Yonge et al, 2013) detailed the dissemination of photovoice data to reach community partners and policy makers. Despite limited studies describing data dissemination, many articles included either a group discussion or a critical dialogue component, which is integral to the photovoice process (Wang & Burris, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are examples of CBPR learning opportunities for graduate professional students ( 12 ), and some models from training opportunities for undergraduate nursing students ( 13 , 14 ). However, we found few examples of undergraduate courses that offer both training in CBPR research fundamentals and applications of these lessons through direct and intensive engagement in research by partnering with community organizations and communities ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%